Anatomy of Inferior Temporal Arteries in Relation to Middle Cranial Fossa Structures: A Postmortem Computed Tomography Angiography Study - Bubenikova, Adela; Giammattei, Lorenzo; Bruguier, Christine; Dunet, Vincent; Starnoni, Daniele; Gonzalez-Lopez, Pablo; George, Mercy; Peters, David; Cossu, Giulia; Benes, Vladimir; Messerer, Mahmoud; Magnin, Virginie; Grabherr, Silke; Daniel, Roy Thomas (Journal of Neurological Surgery Part B: Skull Base, 2024)
The inferior temporal arteries (ITAs), branches of the posterior cerebral artery (PCA), are critical vascular structures encountered during subtemporal surgical approaches. Anatomical data based on multiphase postmortem computed tomography angiography (MPMCTA) are provided as a tool for preoperative surgical planning to lower the risk of ITA injury.Adult (≥18 years) cases that underwent MPMCTA during 2015 to 2023 and whose cause of death did not involve the cerebral circulation were included in the study. Standardized measurements on four predefined coronal slices in relation to the posterior clinoid process (PCP) were established with references to projections in axial and sagittal planes. The main aim was to assess the presence, width, and course of anterior ITA (AITA), middle ITA (MITA), and posterior (PITA) particularly within the individual established quadrants of the middle cranial fossa.A total of 74 hemispheres were studied among 37 patients with the mean age of 52 ± 20.2 years. PITA was present in 98.7% of studied hemispheres, followed by MITA in 90.7% and AITA in 89.2%. The course of PITA was straight (65.8%) or oblique (34.3%), with significant difference in mean width (p = 0.050), branching angle (p < 0.001), distance to tentorial hiatus (p < 0.001), and superior petrosal sinus (p < 0.001). A pattern of PITA loop was defined as a twisting of its course within the collateral sulcus. Significant relationship between the presence of AITA and MITA (p < 0.001) along with the co-presence of AITA and PITA (p = 0.029) was found.Knowledge of ITA characteristics and their relationship to surrounding anatomical structures is vital in subtemporal neurosurgical interventions. Preoperative inspection of the collateral sulcus and its relation to the surgical trajectory is critical to prevent PITA injury.
Keywords: inferior temporal artery; postmortem imaging; surgical planning; posterior cerebral artery